Periaortitis, Coronary Vasculitis and Retro-Orbital Pseudotumor in a Patient with Immunoglobulin G4-Related Sclerosing Vasculitis - Burak BİLGİN and Yakup YEŞİLKAYA and Burcu TÜRKER and Özkan VARAN and Öznur AYDIN and Metin IŞIK and Levent KILIÇ and İsmail DOĞAN and; k BOLAYIR and; t KİRAZ and et al. (Archives of Rheumatology, 2012)
Immunoglobulin G4 (IgG4)-related sclerosing vasculitis is characterized by extensive IgG4-positive plasma cells and T-lymphocyte infiltration of various organs. Serum IgG4 level and immunostaining with anti-IgG4 antibody are useful for the diagnosis. In this article, a 61-year-old male patient who was admitted with the complaints of dyspnea, diffuse edema and chest pain and presented with increased pericardial fluid and serum IgG4 level was reported. Thoracoabdominal computed tomography (CT) scan demonstrated a soft tissue mass starting at arcus aorta and surrounding thoracal and abdominal aorta. After biopsy was obtained, the patient was diagnosed with IgG4-related sclerosing vasculitis.